Tinjauan Yuridis Kedudukan Harta Suami Istri Sebelum dan Sesudah Terjadinya Perkawinan(Studi Kasus Penetapan 39/Pdt/2018/PN Madiun) - James Ng; Cynthia Phinaldo; Belinda Nathania; Aisyah Aisyah (Mahesa Research Center, 2021)
The making of the marriage agreement and the amendment to the marriage agreement are determined and made with the mutual agreement of both parties, in this case, the intention is that the agreement on the making of the marriage agreement is a free agreement and there is no coercion from any party. The purpose of this journal is to find out the share of division between husband and wife’s assets based on the provisions of the applicable laws and regulations, to find out the rules governing the position of husband and wife's assets before and after the occurrence. The research method used by author in this study is the normative method based on data sources, which requires secondary data. Inherited property is assets obtained from each prospective of husband and wife, the property is fully controlled by the owner of the property and cannot be mixed by other parties. The position of husband and wife's assets after the marriage is actually joint property, if there is no agreement to separate the assets, then after the issuance of the letter of determination of assets, the assets obtained after the issuance of the determination letter will become personal or individual property.